A Framework for Seeking the Connections between Technology, Pedagogy and Culture: A study in the Maldives - Aminath Shafiya Adam (Flexible Learning Association of New Zealand, 2017)
Educational technology researchers often overlooked the impact of culture on teachers' use of digital technologies in their pedagogical practices. This also includes a number of technology integration models (e.g. TAM and TPACK) that have failed to explain the connections between technology, pedagogy, and culture. This paper argues that teachers' pedagogical and technological practices cannot be fully understood without considering the social and cultural norms of their specific cultures. This study adopted an ethnographic methodology, linked with Bourdieu's (1977) habitus as a lens for exploring teacher educators' practices in the Maldives. Data were gathered from eleven teacher educators who work in a Maldivian university context: using interviews, observations, focus groups and the hanging out approach. Key findings demonstrated that teacher educators' pedagogical and technological practices were influenced by their own culture, early learning experiences in the Maldives, and their workplace (institutional context). Through this finding, this research proposes a framework, namely, Pedagogical and Technological Cultural Habitus (PATCH) for understanding teachers' pedagogical and technological habitus in various contexts. The PATCH framework is, theoretically useful for designing technology-oriented professional development for professionals in various pedagogical contexts including virtual and blended pedagogical spaces. It also contributes to TPACK framework by adding an outer layer to its current theorisation to represent teachers' backgrounds and habitus when examining their practices.